Premature Death of a Schizophrenic Patient due to Evacuation after a Nuclear Disaster in Fukushima - Yuki Sonoda; Akihiko Ozaki; Arinobu Hori; Asaka Higuchi; Yuki Shimada; Kana Yamamoto; Tomohiro Morita; Toyoaki Sawano; Claire Leppold; Masaharu Tsubokura (Case Reports in Psychiatry)
Although psychiatric patients are likely to be adversely impacted by disasters, information regarding the processes involved in adverse impacts is limited. In March 2011, Japan experienced an earthquake, tsunami, and the Fukushima Daiichi Nuclear Power Plant accident. In its aftermath, Takano Hospital, 22 km south of the power plant, underwent forced patient evacuation. A 54-year-old Japanese male with schizophrenia, who had been hospitalized in the psychiatric ward for over 20 years, was transferred and experienced a series of hospital relocations. Although his physical status was intact when he left Takano Hospital, his condition gradually worsened, presumably due to incomplete exchange of patient information between institutions and changes in the treatment environment. Having developed ileus a few days prior, he was bedridden when he returned to Takano Hospital in May 2011. Over the course of treatment, he developed aspiration pneumonia and died in August 2011. A review of medical records revealed that all his purgative medicines had been stopped after his evacuation, possibly contributing to the development of ileus. This case highlights the necessity of establishing systems enabling patient information sharing between institutions in disaster settings and the importance of recognizing that long-term evacuation may have fatal impacts for psychiatric patients.